Resposta de um monitor de produtividade com sensor ótico a variações de produtividade em arroz irrigado - Aurélio, Niumar Dutra (2011)
Precision Farming (PF) has been studied mainly in soybean, corn and wheat crops, and its use has been increasing in commercial fields. However, in irrigated rice crop, the use of this technology has not yet been fully evaluated, as well as its tools, machinery and equipment such as yield mapping systems. This study aimed to evaluate the precision and accuracy of the response to variations in grain flow of a yield mapping system equipped with an optical sensor in irrigated rice crop both in leveled or non leveled fields. The evaluations were carried out during the 2008/2009 agricultural season on a commercial farm located in the city of Cachoeira do Sul-RS. This evaluation analyzed the behavior of the system when submitted to increased and decreased variations of flow as well as abrupt changes in grain flow using plots that simulated the innumerous situations that occur in a field. To evaluate the behavior of the system, parallel instrumentation was installed on the same harvester, which served as reference. Under the evaluated conditions, the system, presented distortions in accuracy, not responding adequately to all the variations it was submitted to. In the accumulated weight evaluation of each plot, the percentage difference was greater than 3% in almost all the treatments. The results indicate that the evaluated yield monitor did not have satisfactory performance in most of the treatments applied. The Yield data had its quality reduced by the inaccuracy of the speed data provided by the GPS receiver, which makes it unsuitable tool for PF in irrigated rice.crop.